Scattering in Geometric Approach to Quantum Theory - Albert Schwarz (Universe, 2022)
We define inclusive scattering matrix in the framework of a geometric approach to quantum field theory. We review the definitions of scattering theory in the algebraic approach and relate them to the definitions in the geometric approach.